Enhancing Room Reservations Efficiency: The Development of the PTTA Booking System - Han, Siaw Wee; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2025)
Perpustakaan Tun Tungku Aminah (PTTA) relied on manual techniques like phone reservations and Google Forms, resulting from the lack of an online booking mechanism. The objective of this system is to propose using a structured approach to design and develop a customised booking system for the library. The project aims to use an Agile approach to design and develop a customised room booking system for the library. Key library operations such as booking processing, user accommodations, account administration, and reporting are intended to be streamlined by this system. In general, it will offer an online booking platform for library spaces, greatly enhancing record-keeping, information retrieval, and booking administration responsibilities for both staff and patrons.